IMPLEMENTASI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KABUPATEN OGAN KOMERING ULU - Eva Susanti; Ikang Putra Anggara; Wahyu Agil Wijaya (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
The City Without Slums Program (Kotaku) is a program of the Kementrian Pekerjaan Umum dan Perumahan that aims to eradicate the slum areas of the closest urban village to the city, this program has the aim of creating a clean, safe and comfortable area in accordance with the 1945 Constitution article 28H paragraph 1 states that